PERENCANAAN PAJAK DAN BOOK TAX DIFFERENCES TERHADAP PERSISTENSI LABA DENGAN VARIABEL MODERATING KUALITAS LAB - Lestari, Risti Dwi; Rachmawati, Sistya (Indonesian Journal of Accounting and Governance, 2018)
This study aims to analyze and find evidence of the effect of tax planning and book tax differences onearnings persistence with earnings quality as moderating variable. The data used is secondary dataobtained from the financial statements of manufacturing companies listed on the Indonesian StockExchange for 4 years; namely 2014-2017 selected by purposive sampling method. This analyticalmethod used to test the hypothesis in this study is multiple regression analysis.The results of this studyindicate that the tax planning variable has a negative influence on earnings persistence. This isbecause tax planning is used to apply discretion policy of accounting in reducing company profit so itwill reduce tax amount. Contra effect of tax planning causes low earnings persistence The companyconducts tax planning to minimize the tax burden that is borne by companies that have a long-termfocus so that profits can reflect future earnings (sustainable earnings). Whereas book tax differencesdo not have an influence on earnings persistence, this is possible because income and costs that areadjusted in fiscal reconciliation do not affect future earnings revisions. Lastly, earnings quality doesnot strengthen tax planning and book tax differences toward earnings persistence.